Інформаційна система автоматизації роботи закладів харчування - Омельяненко, Андрій; Шаховська, Наталія (Видавництво Львівської політехніки, 2016)
In this work was developed a system of automation of catering. Was performed analysis of technologies and techniques for building such systems, analysis of existing systems and their disadvantages. Created system of automation of catering that provides access to information about the various cafes and restaurants.
Keywords: автоматизовані системи; мобільні пристрої; громадське харчування; заклади харчування; доступ до інформації; функціонал для відвідувача; ресторанний бізнес